Eng Breaking’s Three Techniques to Speak English Like a Native Speaker: A Response Paper (Tarbiyah Suska Conference Series, 2022)
This article aims to deliver the writer’s reaction towards the Eng Breaking claim’s that the online course helps the learners to speak English like a native speaker. In reality, native speakerism is more like a marketing strategy to persuade the English language learners to buy their product rather than a true promise which will come true. A pile of research in second language acquisition has reported that the likely of non-native speakers to achieve nativelike proficiency is slim. There are many factors which prevent it from happening, like learner’s age of learning, method, materials, motivation, and learning environment. Furthermore, the writer uses the literature of second language acquisition studies to support her arguments to counter the Eng Breaking’s claim as a face value promise. The writer also discusses the Eng Breaking three techniques of learning English from the literature point of view. The writer argues that the learning techniques can help the learners to learn English but not likely will lead the learners to possess the native speaker proficiency. In conclusion, the writer sums up that Eng Breaking online course is just a normal English course, whereas native speakerism is exercised and sponsored to merely attract lay people to spend their money into buying their product.Keywords: Second language; native-speakerism; Eng Breaking.